Free markets versus political consensus: The international competitiveness of societies - Michael Dauderstädt (Intereconomics, 1987)
The debate on international competitiveness in recent years has increasingly focused on the structure of society. International competitiveness is seen not merely as a sign of a country's productive capacity, but also as reflecting the efficiency of its social and political structures. The following article examines the five most important western industrial nations in an attempt to answer the question as to which models of society are Internationally competitive.
Keywords: 330; Economic Systems